Curative ESD for intraepithelial esophageal carcinoma with leiomyoma mimicking submucosal invasive carcinoma - Niimi, Keiko (Baishideng Publishing Group Co., Limited, 2009)
This case report presents a 65-year-old man who developed early esophageal cancer with leiomyoma treated by endoscopic submucosal dissection (ESD). There have been several reports of co-existing superficial esophageal cancer and leiomyoma treated by endoscopic mucosal resection. However, there is no previous report describing the co-existing lesion treated by ESD. In order to determine treatment strategies for esophageal cancer, accurate endoscopic evaluation of the cancerous depth is essential. In the present case, the combination of endoscopic ultrasonography and narrow-band imaging system with magnifying endoscopy was extremely useful to evaluate the superficial esophageal cancer with leiomyoma, which lead to the appropriate treatment, ESD.